2011
DOI: 10.4236/psych.2011.22011
|View full text |Cite
|
Sign up to set email alerts
|

Self-Construal and Subjective Wellbeing in Two Ethnic Communities in Singapore

Abstract: The study reported here addressed two questions concerning the applicability to other collectivist cultures of a model developed on the basis of socially defined self-construals and their consequences for subjective wellbeing (Kwan, Bond, & Singelis, 1997). In contrast to the social centrality of the Singaporean Chinese, Islam enjoys centrality in the Malay community. Is subjective well-being in these two cultures attributable to independent or interdependent self-construal? Do parallel paths to subjective wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Study 1 results replicated previous findings ( Kwan et al, 1997 ; Chang et al, 2011 ; Duan et al, 2013 ; Yu et al, 2016 ), showing that unidimensional independence and life satisfaction are positively and indirectly related, by self-esteem mediating the relationship. A potential explanation of this mediation mechanism is provided by Markus and Kitayama (1991) , who argued that individuals’ own evaluation of their self-worth, which is strongly connected with their life satisfaction, is dependent on the cultural standards encompassed in their self-construal.…”
Section: Study 1: the Relationship Between Unidimensional Independencsupporting
confidence: 83%
“…Study 1 results replicated previous findings ( Kwan et al, 1997 ; Chang et al, 2011 ; Duan et al, 2013 ; Yu et al, 2016 ), showing that unidimensional independence and life satisfaction are positively and indirectly related, by self-esteem mediating the relationship. A potential explanation of this mediation mechanism is provided by Markus and Kitayama (1991) , who argued that individuals’ own evaluation of their self-worth, which is strongly connected with their life satisfaction, is dependent on the cultural standards encompassed in their self-construal.…”
Section: Study 1: the Relationship Between Unidimensional Independencsupporting
confidence: 83%
“…A number of studies have identified differences between East Asian and European-American respondents. East Asian repondents have been found to have a tendency to give less extreme answers than European-Americans (Boehm et al 2011;Chong et al 2011;Hommerich and Klient 2012;Tov and Diener 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Not surprisingly, consumers' likelihood of buying a counterfeit brand is inversely related to the price of the genuine brand. The third and fourth categories refer to the social and cultural context in which the counterfeit purchase decision is made, ranging from cultural norms (Chang et al, 2011;Lai & Zaichkowsky, 1999) to the shopping environment (Leisen & Nill, 2001). For example, consumers are likely to purchase a counterfeit brand when they react more favorably to the shopping environment.…”
Section: Factors Of Purchasing Counterfeitsmentioning
confidence: 99%